Automated Red-Edge Information Feature (ARIF) Program For Vegetation Stress Analysis And Classification. - Mohd Shafri, Helmi Zulhaidi; Roslan, Siti Nur Aliaa (2013)
This paper describes the development of Automated Red-edge Information Feature (ARIF) program for evaluating vegetation stress condition. The program is developed in the Interactive Data Language (IDL) environment and will enable vegetation hyperspectral remote sensing data to be analysed easily in terms of the red-edge position. Results from this program was verified using oil palm data from two (2) states of condition, they are healthy and not healthy. The data was taken using a field spectrometer and the result obtained was analyzed using ARIF. It was formed to correlate very well into the real world condition.